Faktor-Faktor yang Mempengaruhi Minat Nasabah Menggunakan Aplikasi Byond serta Relevansinya Terhadap Maqāṣid Syariah - Hakim , Abdul; Apriliansyah, Ega (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2026)
ABSTRACT The launch of BYOND SuperApp by BSI received a positive national response, yet there is an adoption gap at BSI KCP Cinunuk where the majority of customers have not switched from the legacy app. This study aims to analyze the factors affecting customer interest in using the BYOND app and its relevance to Maqāṣid Sharia. The method used is quantitative with multiple linear regression analysis. Data were collected via questionnaires from 97 active customers at BSI KCP Cinunuk. The findings show that simultaneously, perceived ease of use, usefulness, security, promotion, and Sharia values significantly influence usage interest by 74%. Partially, only perceived usefulness and security are significant determinants. Interestingly, Sharia values do not directly influence interest but serve strategically as value reinforcement aligned with the protection of religion (ḥifẓ al-dīn) and wealth (ḥifẓ al-māl). Managerial implications suggest that BSI should focus strategies on strengthening functional benefits and security systems to accelerate adoption, while positioning Sharia features as a unique competitive advantage in the digital banking ecosystem. Keywords: BYOND App, Customer Interest, Maqāṣid Sharia.